Deciphering the role of signal regulatory protein α in immunotherapy for solid tumors - Zhou, Yulong; Tang, Xiyang; Du, Weiguang; Shu, Chen; Yan, Xiaolong; Ma, Nan; Zhao, Jinbo (Frontiers in Immunology, 2025)
Therapies targeting immune checkpoints like programmed death receptor-1 and programmed death ligand-1 have demonstrated remarkable effectiveness in combating cancer. However, a subset of patients fails to respond to these therapies, underscoring the complexity of tumor immune evasion mechanisms. Exploring innovative immune regulatory targets represents a crucial research priority in this field. Signal regulatory protein α (SIRPα) is an immunosuppressive receptor expressed on myeloid cells that inhibits innate immunity through its interaction with the ligand integrin-associated protein (CD47). Blocking the SIRPα–CD47 axis can enhance myeloid cell-mediated anti-tumor responses and stimulate adaptive immunity, thereby synergizing with therapeutic antibodies and T-cell checkpoint inhibitors. Additionally, tumor-intrinsic SIRPα may facilitate tumor growth and immune evasion. This paper aims to elucidate the mechanisms of SIRPα activity in various cell types, review the advancements in SIRPα-targeted tumor therapies, and highlight the potential research value of tumor-expressed endogenous SIRPα.